In Vitro Cytoprotection of Resveratrol against H2O2-Induced Oxidative Stress and Injury in Astrocytes - Guoqiang Xing; Osarieme Evbuomwan; Zhaozhang Li; Pushpa Sharma (Journal of Behavior Therapy And Mental Health, 2016)
Oxidative stress mediated neural cell death is thought to be involved in the progression of secondary cell injury following brain trauma. Agents that can block oxidative stress-related injury could be potential therapies for TBI. Resveratrol, a polyphenol found in plants and red wine, is cytoprotective due to its potent antioxidant activities. To further understand how resveratrol could affect oxidative stress-induced injury, we hypothesized that the cytoprotective activities of resveratrol could be dose-dependent. In this study, resveratrol-induced cytoprotection was evaluated in cultured astrocytes. Primary rat astrocytes were cultured in T-75 flasks to a confluence of 80% before being plated onto 96-well plates. After 24 hours of acclimation, astrocytes were treated with various doses of hydrogen peroxide (H2O2) (0.1, 0.25, 0.5 and 1 µM) and resveratrol (25, 50, 75, 100 µM), respectively. Cell viability was determined 24 hours later using Alamar Blue Assay. Treatment of astrocytes with 0.5 mM H2O2, left 65% of astrocytes non-viable whereas treatment of astrocytes with 0.1 mM H2O2 had no effect on astrocytes viability; whereas 1 mM, H2O2 caused total loss of astrocyte viability. Resveratrol treatment at 75 µM and 100 µM has reduced 0.5 mM H2O2-induced cytotoxicity in astrocytes by 50%. Immunostaining with GFAP also confirmed these findings about the cytoprotective effects of resveratrol in astrocytes exposed to H2O2. These results suggest that resveratrol could be a potential neuroprotective agent in TBI due to its antioxidant properties. Further studies are needed to evaluate the long- term effects of resveratrol in animal models of TBI.
Keywords: Resveratrol